Use of diamond sensors for a high‐flux, high‐rate X‐ray pass‐through diagnostic. (25th April 2022) - Bohon, J.; Gonzalez, E.; Grace, C.; Harris, C. T.; Jacobsen, B.; Kachiguine, S.; Kim, D.; MacArthur, J.; Martinez-McKinney, F.; Mazza, S.; Nizam, M.; Norvell, N.; et al.
Abstract : Two approaches to the design of a diamond sensor signal path were explored using high‐intensity X‐ray pulses from the LINAC Coherent Light Source at SLAC. Results on the charge‐collection efficiency and signal collection time are presented over a range of approximately four orders of magnitude in the generated electron–hole plasma density. Abstract : X‐ray free‐electron lasers (XFELs) deliver pulses of coherent X‐rays on the femtosecond time scale, with potentially high repetition rates. While XFELs provide high peak intensities, both the intensity and the centroid of the beam fluctuate strongly on a pulse‐to‐pulse basis, motivating high‐rate beam diagnostics that operate over a large dynamic range. The fast drift velocity, low X‐ray absorption and high radiation tolerance properties of chemical vapour deposition diamonds make these crystals a promising candidate material for developing a fast (multi‐GHz) pass‐through diagnostic for the next generation of XFELs. A new approach to the design of a diamond sensor signal path is presented, along with associated characterization studies performed in the XPP endstation of the LINAC Coherent Light Source (LCLS) at SLAC. Qualitative charge collection profiles (collected charge versus time) are presented and compared with those from a commercially available detector. Quantitative results on the charge collection efficiency and signal collection times are presented over a range of approximately four orders of magnitude in the generated electron–hole plasma density.